2011
DOI: 10.1590/s1679-45082011ao2184
|View full text |Cite
|
Sign up to set email alerts
|

Dental caries in children participating in a Dentistry for infants Program

Abstract: Participating in the program positively impacted the infants' oral health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 16 publications
1
6
0
4
Order By: Relevance
“…A great obstacle to the success of preventive programs has been the lack of commitment of families to instruct their children in oral hygiene, ( 9 11 ) besides the early adoption of inadequate habits that cause oral diseases. Behavioral habits such as commitment to attend follow-up visits, ( 12 ) presence of non-cariogenic diet, oral hygiene and duration of night feeding could interfere in maintenance of oral health of a child in early childhood. For example, the assiduity in follow-up visits is the responsibility of the infants families who are participating in preventive programs that show the adherence of families to given information and level of valorization to oral health.…”
Section: Introductionmentioning
confidence: 99%
“…A great obstacle to the success of preventive programs has been the lack of commitment of families to instruct their children in oral hygiene, ( 9 11 ) besides the early adoption of inadequate habits that cause oral diseases. Behavioral habits such as commitment to attend follow-up visits, ( 12 ) presence of non-cariogenic diet, oral hygiene and duration of night feeding could interfere in maintenance of oral health of a child in early childhood. For example, the assiduity in follow-up visits is the responsibility of the infants families who are participating in preventive programs that show the adherence of families to given information and level of valorization to oral health.…”
Section: Introductionmentioning
confidence: 99%
“…This can be explained by the progression of the disease, as abscesses may appear, damage of permanent teeth, painful symptomatology, feeding, swallowing, breathing damages 18,19 . Initially, it manifests itself through white and opaque patches, but with progression the clinical aspects become cavitations.…”
Section: Resultsmentioning
confidence: 99%
“…It is essential to make parents or caregivers aware of the importance of oral health of children with guidelines on how to maintain it, including oral hygiene before bed, dental care before 12 months of age to limit or prevent cases of early decay, as well as the integrated assistance of health professionals: surgeon-dentist and pediatrician 13,14 . In the study carried out by Robles et al 15 , the mothers reported having knowledge about the importance of brushing after meals, the relationship between the high carbohydrate diet and the development of caries and its consequences.…”
Section: Discussionmentioning
confidence: 99%
“…It is essential to make parents or caregivers aware of the importance of oral health of children with guidelines on how to maintain it, including oral hygiene before bed, dental care before 12 months of age to limit or prevent cases of early decay, as well as the integrated assistance of health professionals: surgeon-dentist and pediatrician 13,14 .…”
Section: Discussionmentioning
confidence: 99%
“…Early caries brings physical and psychological consequences, since it interferes in the quality of life 18 . This can be explained by the progression of the disease, as abscesses may appear, damage of permanent teeth, painful symptomatology, feeding, swallowing, breathing damages 19 .…”
Section: Discussionmentioning
confidence: 99%